Kekerabatan rayap tanah Macrotermes gilvus Hagen (Blattodea: Termitidae) dari dua habitat di Bogor - Nadzirum Mubin; Idham Sakti Hararap; Giyanto Giyanto; Rika Raffiudin (Jurnal Entomologi Indonesia, 2015)
Subterranean termites Macrotermes gilvus (Hagen) (Blattodea: Termitidae) belongs to the subfamily Macrotermitinae they are distributed widely in Southeast Asia such as Indonesia, Malaysia, Singapore, Myanmar, Philippine, Vietnam, and Thailand. Many studies on these termites have been conducted, but the study of relatedness termites from different locations are barely done. The objective of this study was analyze the relatedness between subterranean termites M. gilvus in IPB Dramaga Campus and Yanlappa Nature Reserve, Jasinga-Bogor. The termite relatedness was analyzed with agonistic behavioral approach and molecularly, technique using mitochondrial COI gene. Termites from both locations showed identical molecular relatedness, however behavioral analysis show that they belong from different parental lineages. Agonistic assessment showed that individuals from different habitat showed aggressive behaviour, whereas those that originated from the same nest do not show any aggression. Molecular detection however have failed to show.